Perancangan Situs Web pada Ocean.com - Humdiana Roelly S.Kom., MM., M.Kom (Jurnal Informatika dan Bisnis, 2012)
The  internet  development  is  now  very  advanced.  With  internet,  we  can  see  many  things  like  the  latest  news,  specifications  of a  product, or purchase a  product  through  a  website which provides sales services. Many company or individual already use the internet to sell  their products. By selling through the internet, making the boundaries of time and distance to be no problem anymore.  Website for Ocean.com store developed using HTML, PHP, and Javascript for the system and using MySQL for the database.  Information  collection  and  user  needs  was  conducted  by  interviewing  Ocean.com  store  owner.  This  website  designed  by  using  object  oriented  analysis  and  design  which  are  depicted with usecase diagrams, sequence diagrams and class diagrams.  The results of this research is a web site that provides services to see information about the  products sold in Ocean.com store and to conduct the sale of products on-line.   With  the  existence  of  website  on  Ocean.com  store  can  improve  services,  facilitate  the transaction, providing information to buyers and expand market share at Ocean.com store.